2013
DOI: 10.1186/scrt234
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia preconditioned bone marrow mesenchymal stem cells promote liver regeneration in a rat massive hepatectomy model

Abstract: IntroductionBone marrow mesenchymal stem cells (BMMSCs) have been reported to facilitate liver regeneration after toxic injuries. However, the effect of BMMSCs on liver regeneration after massive hepatectomy is barely studied. Here we explored whether infusion of BMMSCs promotes liver regeneration in a rat massive hepatectomy model.MethodsHypoxia preconditioning was achieved by culturing BMMSCs under a hypoxia environment. Then 85% hepatectomy was performed and hypoxia or normoxia preconditioned BMMSCs were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 37 publications
2
66
0
Order By: Relevance
“…In addition, we found that among the growth factors and cytokines produced by hypoxic BM-MSCs, VEGF was perhaps the most relevant to MI repair since a strong correlation could be found between the levels of in vitro/in vivo VEGF production and the quantity of neovessel formation in the infarcted zone as revealed by immunohistochemical findings. It has been demonstrated in a rat massive hepatectomy model that administration of hypoxic preconditioned BMSCs was associated with significant elevation of VEGF level in liver homogenate while this effect was blocked by perioperative injection of VEGF neutralized antibody [15]. It is noteworthy that other works have also documented that hypoxia promoted changes in glucose metabolism of MSCs and the latter observation could support the enhancement of FDG uptake evidenced here [41].…”
Section: Discussionsupporting
confidence: 61%
“…In addition, we found that among the growth factors and cytokines produced by hypoxic BM-MSCs, VEGF was perhaps the most relevant to MI repair since a strong correlation could be found between the levels of in vitro/in vivo VEGF production and the quantity of neovessel formation in the infarcted zone as revealed by immunohistochemical findings. It has been demonstrated in a rat massive hepatectomy model that administration of hypoxic preconditioned BMSCs was associated with significant elevation of VEGF level in liver homogenate while this effect was blocked by perioperative injection of VEGF neutralized antibody [15]. It is noteworthy that other works have also documented that hypoxia promoted changes in glucose metabolism of MSCs and the latter observation could support the enhancement of FDG uptake evidenced here [41].…”
Section: Discussionsupporting
confidence: 61%
“…PCNA is associated with regulation of cell proliferation (Yu et al, 2013) and increase in PCNA protein was observed in skeletal myoblasts due to DZ preconditioning (Shao et al, 2012). Bcl 2 is widely studied anti-apoptotic factor (Shao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that during inflammatory state, there is metabolic imbalance at the mucosal surface of the tissues causing hypoxia characterized by over expression of hypoxia inducible factor (HIF) [32,33]. The hypoxia preconditioned BM-MSCs have been used for tissue injury in previous studies considering the MSCs which survives the hypoxic stressed condition are adapted to counteract and survive under the conditions prevailing during the injury for its recovery [34]. In our experiment we have checked the effect of hypoxia on cells as well as on scaffolds which was done after treating the cells grown on scaffold with CoCl 2 .…”
Section: Discussionmentioning
confidence: 99%